Queering the Trans: Gender and sexuality binaries in Icelandic Trans, Queer, and Feminist communities ... - Josephson, Jyl; Einarsdóttir, Þorgerður; Sigurðardóttir, Svandís Anna (Rutgers University, 2016)
Activists in feminist, queer, and trans movements share in common a critique of the existing gender order. Yet activists may have different understandings of what is wrong with existing gender arrangements, and different understandings of what might be required to establish greater social equality. Using data from interviews with activists in the feminist, queer, and trans movements in Iceland, this paper looks at the ways that gender equality and the gender binary is understood by individuals who identify with feminist, queer, and/or trans activism, and some of their shared and conflicting critiques of the existing gender order. ...